Without a prayer : religious expression in public schools - Alley, Robert S., 1932- (Amherst, N.Y. : Prometheus Books, 1996)
Examines the challenges to the ban on school prayer, including protests, legal cases, and threats of violence
Includes bibliographical references and index.
Keywords: Prayer in the public schools -- Law and legislation -- United States